Desain Aplikasi Web Magang Untuk Menunjang Learning Management System Kegiatan Praktik Mengajar di abad Revolusi Industri 4.0. - Andari Puji Astuti; Abdul Aziz; Dwi Anggani Linggar Bharati; Sri Susilogati Sumarni (Universitas Muhammadiyah Semarang, 2018)
It takes an on-line learning system (learning management system) that can be used by prospective teachers, lecturers and tutor teachers. The purpose of this study is to produce educational apprenticeship web design. The type of research is development research. The development research model used is ADDIE. using the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. This research is only up to the web design stage. The results of the study are the results of web-based applications with teacher, student, lecturer and admin users. Each feature is developed with similar content. Keywords: Pembelajaran abad 21, Learning Management System.